2022
DOI: 10.3389/fendo.2022.865909
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Signature Model to Predict the Radioactive Iodine Response of Papillary Thyroid Cancer

Abstract: Papillary thyroid cancer (PTC) accounts for about 90% of thyroid cancer. There are approximately 20%–30% of PTC patients showing disease persistence/recurrence and resistance to radioactive iodine (RAI) treatment. For these PTC patients with RAI refractoriness, the prognosis is poor. In this study, we aimed to establish a comprehensive prognostic model covering multiple signatures to increase the predictive accuracy for progression-free survival (PFS) of PTC patients with RAI treatment. The expression profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Liu et al 21 conducted a retrospective study on 404 patients and demonstrated that primary tumor diameter > 18.5 mm significantly increases the risk of RAIR-DTC. Additionally, Liu et al 29 reported that patients with advanced tumor stage had a higher RAIR rate. In a study conducted by Lee et al, 30 which was in line with a previous report by Tavares et al, 31 NIS expression was inversely correlated with tumor size, this finding implies that NIS depletion occurs as a tumor progresses and that NIS downregulation is likely mediated by molecular mechanisms occurring in the late stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al 21 conducted a retrospective study on 404 patients and demonstrated that primary tumor diameter > 18.5 mm significantly increases the risk of RAIR-DTC. Additionally, Liu et al 29 reported that patients with advanced tumor stage had a higher RAIR rate. In a study conducted by Lee et al, 30 which was in line with a previous report by Tavares et al, 31 NIS expression was inversely correlated with tumor size, this finding implies that NIS depletion occurs as a tumor progresses and that NIS downregulation is likely mediated by molecular mechanisms occurring in the late stages.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted by Liu et al 29 included ribonucleic acid biomarkers (IPCEF1 and hsa-mir-486–5p) in a prognosis prediction model to predict the progression-free survival of PTC patients with RAI therapy.…”
Section: Discussionmentioning
confidence: 99%